2021
DOI: 10.1177/13623613211042135
|View full text |Cite
|
Sign up to set email alerts
|

Quality of the sibling relationship when one sibling has autism spectrum disorder: A randomized controlled trial of a sibling support group

Abstract: When one sibling has autism spectrum disorder, the sibling relationship is often characterized by poorer quality with fewer interactions. Because sibling relationships provide a vital social framework for development, they have the capacity to be a risk or protective factor, depending on the quality of the relationship. One way to improve the quality of the sibling relationship is through typically developing sibling participation in a support group. In this study, researchers randomly assigned typically devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Seven studies used a parallel parent education component to improve parent-reported understanding of siblings' needs and parent-child communication. In two intervention groups, learning about autism and building coping strategies led to significant improvements in siblingreported sibling relationship quality (Zucker et al, 2021) and psychological functioning (Jones et al, 2020), not evidenced in the active comparison groups without an autism-focussed psychoeducational component. Coping skills were also targeted using psychoeducation; these were measured in five quantitative, two mixed methods and all qualitative studies.…”
Section: Theme 2: Knowledge and Educationmentioning
confidence: 91%
See 4 more Smart Citations
“…Seven studies used a parallel parent education component to improve parent-reported understanding of siblings' needs and parent-child communication. In two intervention groups, learning about autism and building coping strategies led to significant improvements in siblingreported sibling relationship quality (Zucker et al, 2021) and psychological functioning (Jones et al, 2020), not evidenced in the active comparison groups without an autism-focussed psychoeducational component. Coping skills were also targeted using psychoeducation; these were measured in five quantitative, two mixed methods and all qualitative studies.…”
Section: Theme 2: Knowledge and Educationmentioning
confidence: 91%
“…These studies found larger positive effects on self-esteem, family wellbeing and knowledge of disability post-intervention and consistently indicated that siblings in the intervention groups appeared to benefit more than those in the comparison group (Giallo & Gavidia-Payne, 2008;Phillips, 1999;Williams et al, 2003). Siblings in interventions with combined psychosocial and educational components appeared to have better outcomes post-intervention than those with only social activities (Brouzos et al, 2017;Haukeland et al, 2020;Williams et al, 2003;Zucker et al, 2021), as were siblings in programs with parallel parenting education (compared to studies without parental involvement; Lobato & Kao, 2002;Roberts et al, 2015).…”
Section: Summary Of Individual Study Findingsmentioning
confidence: 96%
See 3 more Smart Citations